## General

Display information for equation id:KLS:01.05:01 on revision:1987

* Page found: The binomial theorem and other summation formulas (eq KLS:01.05:01)

(force rerendering)

Occurrences on the following pages:

Hash: 1b67570ef242b9b589cf710eaebfd2ac

TeX (original user input):

{\displaystyle
\index{Binomial theorem}\index{Summation formula!Binomial theorem}
\HyperpFq{1}{0}@@{a}{-}{z}=\sum_{n=0}^{\infty}\frac{\pochhammer{a}{n}}{n!}z^n=(1-z)^{-a}
}


### LaTeXML (experimental; uses MathML) rendering

MathML (9.251 KB / 1.605 KB) :

${\displaystyle{\displaystyle{\displaystyle{}{}\HyperpFq{1}{0}@@{a}{-}{z}=\sum_% {n=0}^{\infty}\frac{{\left(a\right)_{n}}}{n!}z^{n}=(1-z)^{-a}}}}$
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle{\displaystyle{\displaystyle{}{}\HyperpFq{1}{0}@@{a}{-}{z}=\sum_%&#10;{n=0}^{\infty}\frac{{\left(a\right)_{n}}}{n!}z^{n}=(1-z)^{-a}}}}" display="inline">
<semantics id="p1.1.m1.1a">
<mrow id="p1.1.m1.1.23" xref="p1.1.m1.1.23.cmml">
<mrow id="p1.1.m1.1.23.2" xref="p1.1.m1.1.23.2.cmml">
<mrow id="p1.1.m1.1.23.2.1" xref="p1.1.m1.1.23.2.1.cmml">
<merror class="ltx_ERROR undefined undefined" id="p1.1.m1.1.1" xref="p1.1.m1.1.1b.cmml">
<mtext id="p1.1.m1.1.1a" xref="p1.1.m1.1.1b.cmml">\HyperpFq</mtext>
</merror>
<mo id="p1.1.m1.1.23.2.1.1" xref="p1.1.m1.1.23.2.1.1.cmml">⁢</mo>
<mn id="p1.1.m1.1.3" xref="p1.1.m1.1.3.cmml">10</mn>
<mo id="p1.1.m1.1.23.2.1.1a" xref="p1.1.m1.1.23.2.1.1.cmml">⁢</mo>
<mi mathvariant="normal" id="p1.1.m1.1.4" xref="p1.1.m1.1.4.cmml">@</mi>
<mo id="p1.1.m1.1.23.2.1.1b" xref="p1.1.m1.1.23.2.1.1.cmml">⁢</mo>
<mi mathvariant="normal" id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">@</mi>
<mo id="p1.1.m1.1.23.2.1.1c" xref="p1.1.m1.1.23.2.1.1.cmml">⁢</mo>
<mi id="p1.1.m1.1.6" xref="p1.1.m1.1.6.cmml">a</mi>
</mrow>
<mo id="p1.1.m1.1.7" xref="p1.1.m1.1.7.cmml">-</mo>
<mi id="p1.1.m1.1.8" xref="p1.1.m1.1.8.cmml">z</mi>
</mrow>
<mo id="p1.1.m1.1.9" xref="p1.1.m1.1.9.cmml">=</mo>
<mrow id="p1.1.m1.1.23.3" xref="p1.1.m1.1.23.3.cmml">
<mstyle displaystyle="true" id="p1.1.m1.1.23.3.1" xref="p1.1.m1.1.23.3.1.cmml">
<munderover id="p1.1.m1.1.23.3.1a" xref="p1.1.m1.1.23.3.1.cmml">
<mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.10" xref="p1.1.m1.1.10.cmml">∑</mo>
<mrow id="p1.1.m1.1.11.1" xref="p1.1.m1.1.11.1.cmml">
<mi id="p1.1.m1.1.11.1.1" xref="p1.1.m1.1.11.1.1.cmml">n</mi>
<mo id="p1.1.m1.1.11.1.2" xref="p1.1.m1.1.11.1.2.cmml">=</mo>
<mn id="p1.1.m1.1.11.1.3" xref="p1.1.m1.1.11.1.3.cmml">0</mn>
</mrow>
<mi mathvariant="normal" id="p1.1.m1.1.12.1" xref="p1.1.m1.1.12.1.cmml">∞</mi>
</munderover>
</mstyle>
<mrow id="p1.1.m1.1.23.3.2" xref="p1.1.m1.1.23.3.2.cmml">
<mstyle displaystyle="true" id="p1.1.m1.1.13" xref="p1.1.m1.1.13.cmml">
<mfrac id="p1.1.m1.1.13a" xref="p1.1.m1.1.13.cmml">
<msub id="p1.1.m1.1.13.2.1.6" xref="p1.1.m1.1.13.2.1.1.cmml">
<mrow id="p1.1.m1.1.13.2.1.6.2" xref="p1.1.m1.1.13.2.1.1.cmml">
<mo id="p1.1.m1.1.13.2.1.2" xref="p1.1.m1.1.13.2.1.1.1.cmml">(</mo>
<mi id="p1.1.m1.1.13.2.1.3" xref="p1.1.m1.1.13.2.1.3.cmml">a</mi>
<mo id="p1.1.m1.1.13.2.1.4" xref="p1.1.m1.1.13.2.1.1.1.cmml">)</mo>
</mrow>
<mi id="p1.1.m1.1.13.2.1.5.1" xref="p1.1.m1.1.13.2.1.5.1.cmml">n</mi>
</msub>
<mrow id="p1.1.m1.1.13.3" xref="p1.1.m1.1.13.3.cmml">
<mi id="p1.1.m1.1.13.3.1" xref="p1.1.m1.1.13.3.1.cmml">n</mi>
<mo lspace="0pt" rspace="3.5pt" id="p1.1.m1.1.13.3.2" xref="p1.1.m1.1.13.3.2.cmml">!</mo>
</mrow>
</mfrac>
</mstyle>
<mo id="p1.1.m1.1.23.3.2.1" xref="p1.1.m1.1.23.3.2.1.cmml">⁢</mo>
<msup id="p1.1.m1.1.23.3.2.2" xref="p1.1.m1.1.23.3.2.2.cmml">
<mi id="p1.1.m1.1.14" xref="p1.1.m1.1.14.cmml">z</mi>
<mi id="p1.1.m1.1.15.1" xref="p1.1.m1.1.15.1.cmml">n</mi>
</msup>
</mrow>
</mrow>
<mo id="p1.1.m1.1.16" xref="p1.1.m1.1.16.cmml">=</mo>
<msup id="p1.1.m1.1.23.4" xref="p1.1.m1.1.23.4.cmml">
<mrow id="p1.1.m1.1.23.4.2" xref="p1.1.m1.1.23.4.2.2.cmml">
<mo stretchy="false" id="p1.1.m1.1.17" xref="p1.1.m1.1.23.4.2.2.cmml">(</mo>
<mrow id="p1.1.m1.1.23.4.2.2" xref="p1.1.m1.1.23.4.2.2.cmml">
<mn id="p1.1.m1.1.18" xref="p1.1.m1.1.18.cmml">1</mn>
<mo id="p1.1.m1.1.19" xref="p1.1.m1.1.19.cmml">-</mo>
<mi id="p1.1.m1.1.20" xref="p1.1.m1.1.20.cmml">z</mi>
</mrow>
<mo stretchy="false" id="p1.1.m1.1.21" xref="p1.1.m1.1.23.4.2.2.cmml">)</mo>
</mrow>
<mrow id="p1.1.m1.1.22.1" xref="p1.1.m1.1.22.1.cmml">
<mo id="p1.1.m1.1.22.1.1" xref="p1.1.m1.1.22.1.1.cmml">-</mo>
<mi id="p1.1.m1.1.22.1.2" xref="p1.1.m1.1.22.1.2.cmml">a</mi>
</mrow>
</msup>
</mrow>
<annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
<apply id="p1.1.m1.1.23.cmml" xref="p1.1.m1.1.23">
<and id="p1.1.m1.1.23a.cmml" xref="p1.1.m1.1.23"/>
<apply id="p1.1.m1.1.23b.cmml" xref="p1.1.m1.1.23">
<eq id="p1.1.m1.1.9.cmml" xref="p1.1.m1.1.9"/>
<apply id="p1.1.m1.1.23.2.cmml" xref="p1.1.m1.1.23.2">
<minus id="p1.1.m1.1.7.cmml" xref="p1.1.m1.1.7"/>
<apply id="p1.1.m1.1.23.2.1.cmml" xref="p1.1.m1.1.23.2.1">
<times id="p1.1.m1.1.23.2.1.1.cmml" xref="p1.1.m1.1.23.2.1.1"/>
<ci id="p1.1.m1.1.1b.cmml" xref="p1.1.m1.1.1">
<merror class="ltx_ERROR undefined undefined" id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">
<mtext id="p1.1.m1.1.1a.cmml" xref="p1.1.m1.1.1">\HyperpFq</mtext>
</merror>
</ci>
<cn type="integer" id="p1.1.m1.1.3.cmml" xref="p1.1.m1.1.3">10</cn>
<ci id="p1.1.m1.1.4.cmml" xref="p1.1.m1.1.4">@</ci>
<ci id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5">@</ci>
<ci id="p1.1.m1.1.6.cmml" xref="p1.1.m1.1.6">𝑎</ci>
</apply>
<ci id="p1.1.m1.1.8.cmml" xref="p1.1.m1.1.8">𝑧</ci>
</apply>
<apply id="p1.1.m1.1.23.3.cmml" xref="p1.1.m1.1.23.3">
<apply id="p1.1.m1.1.23.3.1.cmml" xref="p1.1.m1.1.23.3.1">
<csymbol cd="ambiguous" id="p1.1.m1.1.23.3.1.1.cmml" xref="p1.1.m1.1.23.3.1">superscript</csymbol>
<apply id="p1.1.m1.1.23.3.1.2.cmml" xref="p1.1.m1.1.23.3.1">
<csymbol cd="ambiguous" id="p1.1.m1.1.23.3.1.2.1.cmml" xref="p1.1.m1.1.23.3.1">subscript</csymbol>
<sum id="p1.1.m1.1.10.cmml" xref="p1.1.m1.1.10"/>
<apply id="p1.1.m1.1.11.1.cmml" xref="p1.1.m1.1.11.1">
<eq id="p1.1.m1.1.11.1.2.cmml" xref="p1.1.m1.1.11.1.2"/>
<ci id="p1.1.m1.1.11.1.1.cmml" xref="p1.1.m1.1.11.1.1">𝑛</ci>
<cn type="integer" id="p1.1.m1.1.11.1.3.cmml" xref="p1.1.m1.1.11.1.3">0</cn>
</apply>
</apply>
<infinity id="p1.1.m1.1.12.1.cmml" xref="p1.1.m1.1.12.1"/>
</apply>
<apply id="p1.1.m1.1.23.3.2.cmml" xref="p1.1.m1.1.23.3.2">
<times id="p1.1.m1.1.23.3.2.1.cmml" xref="p1.1.m1.1.23.3.2.1"/>
<apply id="p1.1.m1.1.13.cmml" xref="p1.1.m1.1.13">
<divide id="p1.1.m1.1.13.1.cmml" xref="p1.1.m1.1.13"/>
<apply id="p1.1.m1.1.13.2.1.1.cmml" xref="p1.1.m1.1.13.2.1.6">
<csymbol cd="dlmf" id="p1.1.m1.1.13.2.1.1.1.cmml" xref="p1.1.m1.1.13.2.1.2">Pochhammer-symbol</csymbol>
<ci id="p1.1.m1.1.13.2.1.3.cmml" xref="p1.1.m1.1.13.2.1.3">𝑎</ci>
<ci id="p1.1.m1.1.13.2.1.5.1.cmml" xref="p1.1.m1.1.13.2.1.5.1">𝑛</ci>
</apply>
<apply id="p1.1.m1.1.13.3.cmml" xref="p1.1.m1.1.13.3">
<factorial id="p1.1.m1.1.13.3.2.cmml" xref="p1.1.m1.1.13.3.2"/>
<ci id="p1.1.m1.1.13.3.1.cmml" xref="p1.1.m1.1.13.3.1">𝑛</ci>
</apply>
</apply>
<apply id="p1.1.m1.1.23.3.2.2.cmml" xref="p1.1.m1.1.23.3.2.2">
<csymbol cd="ambiguous" id="p1.1.m1.1.23.3.2.2.1.cmml" xref="p1.1.m1.1.23.3.2.2">superscript</csymbol>
<ci id="p1.1.m1.1.14.cmml" xref="p1.1.m1.1.14">𝑧</ci>
<ci id="p1.1.m1.1.15.1.cmml" xref="p1.1.m1.1.15.1">𝑛</ci>
</apply>
</apply>
</apply>
</apply>
<apply id="p1.1.m1.1.23c.cmml" xref="p1.1.m1.1.23">
<eq id="p1.1.m1.1.16.cmml" xref="p1.1.m1.1.16"/>
<share href="#p1.1.m1.1.23.3.cmml" id="p1.1.m1.1.23d.cmml" xref="p1.1.m1.1.23"/>
<apply id="p1.1.m1.1.23.4.cmml" xref="p1.1.m1.1.23.4">
<csymbol cd="ambiguous" id="p1.1.m1.1.23.4.1.cmml" xref="p1.1.m1.1.23.4">superscript</csymbol>
<apply id="p1.1.m1.1.23.4.2.2.cmml" xref="p1.1.m1.1.23.4.2">
<minus id="p1.1.m1.1.19.cmml" xref="p1.1.m1.1.19"/>
<cn type="integer" id="p1.1.m1.1.18.cmml" xref="p1.1.m1.1.18">1</cn>
<ci id="p1.1.m1.1.20.cmml" xref="p1.1.m1.1.20">𝑧</ci>
</apply>
<apply id="p1.1.m1.1.22.1.cmml" xref="p1.1.m1.1.22.1">
<minus id="p1.1.m1.1.22.1.1.cmml" xref="p1.1.m1.1.22.1.1"/>
<ci id="p1.1.m1.1.22.1.2.cmml" xref="p1.1.m1.1.22.1.2">𝑎</ci>
</apply>
</apply>
</apply>
</apply>
</annotation-xml>
<annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle{\displaystyle{\displaystyle{}{}\HyperpFq{1}{0}@@{a}{-}{z}=\sum_%
{n=0}^{\infty}\frac{{\left(a\right)_{n}}}{n!}z^{n}=(1-z)^{-a}}}}</annotation>
</semantics>
[/itex]


SVG (12.37 KB / 3.993 KB) :

### SVG (MathML can be enabled via browser plugin) rendering

MathML (0 B / 8 B) :

Failed to get svg.

In Maple:

In Mathematica:

## Similar pages

Calculated based on the variables occurring on the entire The binomial theorem and other summation formulas page

## Identifiers

### MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results